Surgical fixation of metastatic spine fractures: 6-months experience at a cancer hospital from a developing country- an audit - Arshad, Ayesha; Irfan Yousaf (Journal of the Pakistan Medical Association, 2022)
Objective: To audit the outcomes in cases of surgical fixation for metastatic spine fractures at a single centre. Method: The retrospective audit was conducted at the Surgical Oncology Department of the Shaukat Khanum Memorial Cancer Hospital, Lahore, Pakistan, and comprised data of all patients who underwent surgery for metastatic spine fractures from December 1, 2019, to May 31, 2020. The patients were followed up for three months after the surgery. Pre-surgery American Spinal Injury Association Impairment Scale grades were compared with post-operative grades for all the patients. Data was analysed using SPSS 20. Results: Of the 16 patients, 12(75%) were females and 4(25%) were males, with an overall mean age of 44.0+/-11.9 years (range: 24-64 years). The only co-morbid was hypertension, which was present in 6(37.5%) patients. The most common primary site was breast 10(62.5%), and 12(75%) patients presented more than 12 months after the initial diagnosis. Lumbar spine was involved in 10(62.5%) cases. Pre-operative American Spinal Injury Association Impairment Scale grade was E in 8(50%) patients. Post-operatively, 14(87.5%) patients had the E grade. There was complication in 1(6.25%) case that had a post-operative wound infection. Conclusion: Surgery for spinal metastases was found to be a safe and viable option for patients with metastatic spine fractures in resource-limited countries like Pakistan. Key Words: Metastasis, Spine, Fractures, Surgical fixation. Continuous...